Estrategias del cuidado humanizado implementadas en las unidades de cuidado crítico neonatal en los últimos 5 años (2022)
Introduction: humanized care in neonatal critical care units turns out to be a challenge for the entire health team, because it implies having the cognitive, psychological, and spiritual capacity to be able to relate to the mother and the hospitalized newborn, in this way avoid factors that may compromise the health of the baby, favoring quality and humanized care. To this end, we must be guided by evidence-based strategies that guarantee the quality of care provided, humanize the entire neonatal care process, and facilitate dynamic interaction between health professionals, the environment, the newborn, and the family, understood as a Unit. Objective: To identify the humanized care strategies implemented in neonatal intensive care units in the last 5 years through a systematic review. Methodology: a search was carried out in different indexed databases, PubMed, scopus, science direct, academic google, Lilacs, SciELO and a subsequent review applying the inclusion and quality criteria to be included in the bibliographic sample. Results: Four categories were found into which the humanization strategies are divided and presented: those focused on the participation of families, non-pharmacological actions used in NICUs, those referring to the physical and technological environment that contributes to improving the care of RN and interventions aimed at strengthening the relationship between the health team and families. Conclusions: According to the evidenced strategies, it is understood that many of the NICUs apply pharmacological and non-pharmacological measures for the management and care of neonates who are undergoing painful interventions and prolonged hospital stays, however, there is little awareness in the processes of attention, to a greater extent in relation to information communication strategies and support groups for parents. It is necessary that the health personnel consider that the premature newborn and/or with health problems is a fragile and competent human being who can communicate and interact with his environment according to his gestational age and his state of development, however evidence that these strategies are cost-effective and easy to apply in health institutions.